Handling of Passenger Arrivals by Sriwijaya Air Cassation Officers at Soetta Airport Tangerang - Khanza Aulia Bilqis, Nabila; Afnan, Dikhorir (Ann Publisher, 2024)
This study aims to determine the process of handling passengers who will transit or stop and the handling of passengers who require special handling. In this study, the authors used descriptive research methods with a qualitative approach. The results of this study explain that the services provided by Sriwijaya Air officers for arrival services, especially in handling transit or transfer passengers and passengers who require special handling at the destination airport, are by procedures. In handling transit passengers, there are two services: when transit passengers do not change planes and when transit passengers change planes. The Sriwijaya Air officer provides particular passenger handling for each passenger category, so there are no errors in passenger service. It can be concluded that the handling of transit or transfer and handling of special passengers is carried out by procedures that are carried out properly by Sriwijaya Air.